Host lysolipid differentially modulates virulence factor expression and antimicrobial susceptibility in Pseudomonas aeruginosa. Issue 7 (7th July 2022) - McSorley, James C.; MacFadyen, Alison C.; Kerr, Leena; Tucker, Nicholas Peter
Abstract : Lysophosphatidic acid (LPA) occurs naturally in inflammatory exudates and has previously been shown to increase the susceptibility of Pseudomonas aeruginosa to β-lactam antibiotics whilst concomitantly reducing accumulation of the virulence factors pyoverdine and elastase. Here it is demonstrated that LPA can also exert inhibitory effects upon pyocyanin production in P. aeruginosa, as well as influencing susceptibility to a wide range of chemically diverse non β-lactam antimicrobials. Most strikingly, LPA markedly antagonizes the effect of the polycationic antibiotics colistin and tobramycin at a concentration of 250 µg ml −1 whilst conversely enhancing their efficacy at the lower concentration of 8.65 µg ml −1, approximating the maximal physiological concentrations found in inflammatory exudates. Transcriptomic responses of the virulent strain UCBPP-PA14 to LPA were analysed using RNA-sequencing along with BioLog phenoarrays and whole cell assays in attempts to delineate possible mechanisms underlying these effects. The results strongly suggest involvement of LPA-induced carbon catabolite repression together with outer-membrane (OM) stress responses whilst raising questions about the effect of LPA upon other P. aeruginosa virulence factors including type III secretion. This could have clinical relevance as it suggests that endogenous LPA may, at concentrations found in vivo, differentially modulate antibiotic susceptibility of P. aeruginosa whilst simultaneously regulating expression of virulence factors, thereby influencing host–pathogen interactions during infection. The possibility of applying exogenous LPA locally as an enhancer of select antibiotics merits further investigation.